Hibah umra and ruqba in islamic law: a legal analysis - Md. Habibur, Rahman; Puspa Liza, Ghazali; Md Faruk, Abdullah (2018)
Hibah umra and ruqba are the two forms of donation the Arabs were dealing with that in pre-Islamic period. It is apparently said that majority of the Muslim jurists are of the opinion that, the temporary or conditional hibah such as umra and ruqba are considered valid but the conditions are considered void. However, there are some stands which opine otherwise. Hence, this research sets out to make a legal study on this issue. The study follows the analytical method. The objective of this paper is to develop the principles and applications of these forms of hibah, ensuring the public wellbeing that conforms to the maqasid al-shari’ah. The research posits that these types of hibah could be the underlying ground for the survivorship principle in the joint tenancy arrangement. Moreover, it also could be one step forward to solve the ownership and hibah issues of the family takaful benefit.